(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Tkachuk I. O. Essence and structure of the phenomenon of «interpretational competence pedagogical college students». The article deals with such notions as «interpretative activity», «interpretative competence»; discloses the nature and structure of the phenomenon of «interpretative competence of students of pedagogical college». It is defined that the structure of interpretative competence of students of pedagogical college contains axiological, cognitive, activity-creative and reflective components with specific characteristics.